Collaborative Learning: Engaging Students in Physics by Overcoming Math Challenges - Suryati Sitepu; M Mardiningsih; Citra Dewi Hasibuan; Maulida Yanti; Enita Dewi Tarigan; Yan Batara Putra Siringoringo; Muthia Ferliani Balqis (PT FORMOSA CENDEKIA GLOBAL, 2024)
This service is carried out to improve the quality of education, especially at SMP Negeri 3 Galang. Students' lack of interest in learning a subject needs to be overcome using a strategy to update learning methods. The method carried out in this service is in the form of training for teachers and students with a Collaborative Learning approach, where students during the learning process are more dominating (student center). The application of the Collaborative Learning model shows positive results, namely teachers gain experience in teaching in an interesting way, and the learning outcomes obtained by students have increased significantly and can be seen from the results of the pre-test and post-test at the time of training. The results of the implementation of this service activity show that the Collaborative Learning learning model is quite effective in improving students' understanding of Mathematics and Physics calculations.